'Rally round the flag': the COVID-19 crisis and trust in the national government. Issue 5 (19th September 2021) - Kritzinger, Sylvia; Foucault, Martial; Lachat, Romain; Partheymüller, Julia; Plescia, Carolina; Brouard, Sylvain
Abstract: During international crises, trust in government is expected to increase irrespective of the wisdom of the policies it pursues. This has been called a 'rally-round-the-flag' effect. This article examines whether the COVID-19 crisis has resulted in such a rally effect. Using multi-wave panel surveys conducted in Austria and France starting from March 2020, in the article it is examined how government trust was affected by the perceived threats to the nation's health and economy created by the pandemic as well as by the perceived appropriateness of the government's crisis response. A strong rally effect is shown in Austria, where trust was closely tied to perceived health risks, but faded away quickly over time. Perceptions of government measures mattered, too, while perceived economic threat only played a minor role. In France, in contrast, a strong partisan divide is found and no rally effect. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2021.1925017 .